Analisis Retorika Edukatif Zhafira Aqyla dalam Menyampaikan Literasi Seksual Islami - Husnan, Shafira Mutia Ramadhanti (Prodi Komunikasi & Penyiaran Islam, Program Pascasarajana, UIN Sunan Gunung Djati Bandung, 2023)
This paper analyzes Zhafira Aqyla's rhetorical model of da'wah as a young educator who actively campaigns for Islamic values-based sexuality education through digital platforms. Zhafira integrates Aristotle's classical rhetorical approach of ethos, pathos, and logos in her communication strategy. Zhafira's rhetorical function is transformational, not only conveying messages, but encouraging social change. She is able to reduce public resistance to the issue of sex education, foster critical awareness in Muslim families, and form a new paradigm in da'wah that is educative, empathetic, and contextual. Thus, Zhafira Aqyla presents a progressive model of da'wah rhetoric that is relevant to the needs of the digital generation and today's socio-religious challenges. Keywords : Zhafira Aqyla, preaching rhetoric, sexuality education